Examining the relationship of inflation, gross domestic product, oil price, foreign direct investment, and trade openness on unemployment in Saudi Arabia - Lansheng Cao; Sayed Fayaz Ahmad; Yajun Wang; Syed Jamal Shah; Muhammad Ibrahim; Fuad Mohammed Alhamdi; Mahmoud Izzat Allaham; Ansar Abbas (Humanities & Social Sciences Communications)
Abstract The study examines the correlation between oil price, foreign direct investment (FDI), trade openness and real gross domestic product (GDP) with the unemployment rate in Saudi Arabia for the period 2016–2023. The study used EViews and excel for the data analysis; and employed Autoregressive Distributed Lag (ARDL) model for the extraction of results. The findings show that oil price FDI, trade openness, inflation and real GDP have significant negative correlation with unemployment rate, and any changes in these factors affect unemployment rate in the long term, with the coefficient −0.063, −1.630, −2.061, −3.170, and −0.353, standard error 0.097, 0.333, 0.716, 0.426, and 0.080 and t-statistics −6.507, −4.900, −2.877, −7.449, and −4.387 respectively. The results indicate that beside oil prices, there are other macroeconomic factors that also influence the unemployment rate, and show the importance of diversification of economy and reducing the reliance on oil. The findings have valuable insights for the economists and policymakers of Saudi Arabia and for other countries which mostly rely on oil exports.